PKM Edukasi Spiritual Bagi Orang Tua Murid Anak Berkebutuhan Khusus (ABK) Menggunakan Alat Permainan Edukatif - Murtiningsih Murtiningsih; Desi Sukmawati; Suyono Untung; Hanif Abdul Latif (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Rumah autis Depok is a Social Welfare Institution that manages schools and therapy for children with special needs, especially for orphans and poor people. Learning during the pandemic is done through a home program. During learning at home, parents experience difficulties due to lack of knowledge and skills in educating children with special needs, so that learning becomes less effective. Changes in behavior occur in Children with Special Needs (ABK), for example being hyperactive or lack of motivation to learn. The spiritual approach is one of the learning methods for children with special needs that can be implemented to provide calm and reduce hyperactivity in children. Based on the analysis of the situation, the DKI Jakarta PKP Health and Technology Institute (IKTJ) provides community service through spiritual education activities for teachers and parents using educational games to meet the spiritual needs of children with special needs. The purpose of providing spiritual education to teachers and parents is to increase the knowledge and skills of parents in educating children to meet the spiritual needs of children with special needs. The method of carrying out activities is the lecture method and online discussion via zoom meet. Evaluation of activities was carried out using a questionnaire to participants. The results of the evaluation showed that there was an increase in parents' knowledge about spiritual aspects. The output of the activity, namely the PKM activity video for spiritual education for children with special needs, has been uploaded to YouTube.